Multifunctional antibody responses from a primate Shigella outbreak inform vaccine design - Robert M. Gallant; Paul Savarino; Sophia Pulido; Morgan S. A. Gilman; Ti Lu; Jennifer Hayes; Nicholas L. Xerri; Torrey Williams; Mark A. Ochoa; Zackary Dietz; Eric Peterson; Timothy Scott; et al. (Science Translational Medicine, 2026)
There is currently no approved vaccine for Shigella spp., a leading cause of diarrhea with increasing rates of antimicrobial resistance. Shigella vaccine development is complicated in part by an incomplete understanding of the structural and molecular determinants of immunity. To address this, we isolated monoclonal antibodies against candidate Shigella vaccine antigens using samples from a Shigella flexneri outbreak in a nonhuman primate (NHP) research facility. We found that antibodies targeting the Shigella O-antigen can undergo substantial affinity maturation (>10%) to acquire broad cross-reactivity across S. flexneri serotypes. We also found that the virulence-associated type III secretion system (T3SS) proteins IpaD and IpaB elicit moderate T cell and robust antibody responses. T3SS antibodies could either inhibit or enhance bacterial virulence in vitro and differed in vivo depending on their epitope specificity. Collectively, these findings provide insights into protective and deleterious immune responses against Shigella that directly inform vaccine immunogen design.